Bioactive and Biological Potential of Black Chokeberry Leaves Under the Influence of Pressurized Liquid Extraction and Microwave-Assisted Extraction - Maja Repajić; Ivona Elez Garofulić; Ena Cegledi; Erika Dobroslavić; Sandra Pedisić; Ksenija Durgo; Ana Huđek Turković; Jasna Mrvčić; Karla Hanousek Čiča; Verica Dragović-Uzelac (Antioxidants)
To determine the optimal conditions of pressurized liquid extraction (PLE) and microwave-assisted extraction (MAE) of polyphenols from black chokeberry leaves (BCL), temperature, time and sample-to-solvent ratio (SSR) were varied to obtain maximum polyphenols yield. The extracts were analyzed for total polyphenols (TP) as well as individual ones (UPLC ESI MS2) and antioxidant capacity (FRAP, DPPH and ORAC). Moreover, the biological activity of the selected extracts was additionally determined. The optimal PLE and MAE conditions were 150 °C, 5 min extraction time and SSR 1:30 g/mL (TP 80.0 mg GAE/g dm), and 70 °C, extraction time 5 min and SSR 1:30 g/mL (TP 36.4 mg GAE/g dm), respectively. Both methods yielded similar polyphenol profiles (43 compounds) but differed quantitatively. MAE extracts contained more flavonols and phenolic acids, while PLE extracts had higher procyanidins and flavan-3-ols. Furthermore, the PLE extract exhibited a superior antioxidant capacity. This BCL extract also showed that it can protect against oxidative and DNA damage and can induce free radical formation and DNA damage, albeit at different doses. Moreover, it had a moderate antimicrobial activity against S. aureus and B. subtilis, while no antimicrobial activity was observed against Gram-negative bacteria as well as yeasts, lactic acid bacteria and molds.